Modulation of ion transport across rat distal colon by cysteine - Diener, Martin (Frontiers in Physiology, 2012)
The aim of this study was to identify the actions of stimulation of endogenous production of H2S by cysteine, the substrate for the two H2S-producing enzymes, cystathionine-β-synthase and cystathionine-γ-lyase, on ion transport across rat distal colon. Changes in short-circuit current (Isc) induced by cysteine were measured in Ussing chambers. Free cysteine caused a concentration-dependent, transient fall in Isc, which was sensitive to amino-oxyacetate and β-cyano-L-alanine, i.e., inhibitors of H2S-producing enzymes. In contrast, Na cysteinate evoked a biphasic change in Isc, i.e., an initial fall followed by a secondary increase, which was also reduced by these enzyme inhibitors. All responses were dependent on the presence of Cl− and inhibited by bumetanide, suggesting that free cysteine induces an inhibition of transcellular Cl− secretion, whereas Na cysteinate – after a transient inhibitory phase – activates anion secretion. The assumed reason for this discrepancy is a fall in the cytosolic pH induced by free cysteine, but not by Na cysteinate, as observed in isolated colonic crypts loaded with the pH-sensitive dye, BCECF. Intracellular acidification is known to inhibit epithelial K+ channels. Indeed, after preinhibition of basolateral K+ channels with tetrapentylammonium or Ba2+, the negative Isc induced by free cysteine was reduced significantly. In consequence, stimulation of endogenous H2S production by Na cysteinate causes, after a short inhibitory response, a delayed activation of anion secretion, which is missing in the case of free cysteine, probably due to the cytosolic acidification. In contrast, diallyl trisulfide, which is intracellularly converted to H2S, only evoked a monophasic increase in Isc without the initial fall observed with Na cysteinate. Consequently, time course and amount of produced H2S seem to strongly influence the functional response of the colonic epithelium evoked by this gasotransmitter.